Pierre Schaeffer e Marcel Proust: as expressões da escuta - Igor Reis Reyner (2012)
Literature on Marcel Prousts À la recherche du temps perdu, however vast, has failed to tackle the Narrators poetics of listening. In order to understand it, excerpts from Le Côté de Guermantes are interpreted with reference to Pierre Schaeffers notions of quatre fonctions de lécoute, of comportement découte and of écoute réduite, formulated in Traité des objets musicaux. In the first chapter, a diachronic study of Schaeffers texts from 1942, 1950 and 1966 shows that écoute réduite is not a compositional aesthetics but a poetics of aural perception. The second chapter relates Schaeffer to Proust through analyses of references to Proust in Schaeffers writings, and of a study by Gilles Deleuze on the role of involuntary memory in the recherche du temps perdu. The third chapter cross-fertilizes listening theory and literature by illustrating theory with excerpts from the novel and comprehending the novels sound space through theory. Excerpts organize themselves according to characters and places so as to be interpreted according to a poetics of that presents itself as a perversion of listening.